Identification and fine mapping of a new gene, BPH31 conferring resistance to brown planthopper biotype 4 of India to improve rice, Oryza sativa L - Prahalada, G.D.; Shivakumar, N.; Lohithaswa, H.C.; Sidde Gowda, D.K.; Ramkumar, G.; Kim, Sung-Ryul; Ramachandra, C.; Hittalmani, Shailaja; Mohapatra, Trilochan; Jena, Kshirod K. (Springer, 2017)
Rice (Oryza sativa L.) is the staple food for more than 3.5 billion people, mainly in Asia. Brown planthopper (BPH) is one of the most destructive insect pests of rice that limits rice production. Host-plant resistance is one of the most efficient ways to overcome BPH damage to the rice crop. Results BPH bioassay studies from 2009 to 2015 conducted in India and at the International Rice Research Institute (IRRI), Philippines, revealed that the cultivar CR2711–76 developed at the National Rice Research Institute (NRRI), Cuttack, India, showed stable and broad-spectrum resistance to several BPH populations of the Philippines and BPH biotype 4 of India. Genetic analysis and fine mapping confirmed the presence of a single dominant gene, BPH31, in CR2711–76 conferring BPH resistance. The BPH31 gene was located on the long arm of chromosome 3 within an interval of 475 kb between the markers PA26 and RM2334. Bioassay analysis of the BPH31 gene in CR2711–76 was carried out against BPH populations of the Philippines. The results from bioassay revealed that CR2711–76 possesses three different mechanisms of resistance: antibiosis, antixenosis, and tolerance. The effectiveness of flanking markers was tested in a segregating population and the InDel type markers PA26 and RM2334 showed high co-segregation with the resistance phenotype. Foreground and background analysis by tightly linked markers as well as using the Infinium 6 K SNP chip respectively were applied for transferring the BPH31 gene into an indica variety, Jaya. The improved BPH31-derived Jaya lines showed strong resistance to BPH biotypes of India and the Philippines. Conclusion The new BPH31 gene can be used in BPH resistance breeding programs on the Indian subcontinent. The tightly linked DNA markers identified in the study have proved their effectiveness and can be utilized in BPH resistance breeding in rice